Meningkatkan Semangat Belajar Siswa Melalui Penggunaan Game Edukasi Berbasis Teknologi Pada Siswa SMP IT Bina Bangsa - Desty Endrawati Subroto; Husna Nabilah; Inggit Eka Wahyuni; Mulyati Mulyati (Fakultas Teknik Universitas Cenderawasih, 2024)
In the current digital era, learning supports students' enthusiasm for learning, there is a lot of learning that can foster enthusiasm for learning, conventional learning sometimes makes students bored in following the learning process. The role of the teacher is also very important in fostering enthusiasm for learning in students, an interesting learning process and an active classroom atmosphere can be a factor in fostering enthusiasm for learning. The learning media that is widely used today is educational games. Educational games are a learning medium that describes a game designed to help the learning process. This socialization activity aims to utilize the use of technology in the field of education by using a game engine. The use of technology in the field of education has also succeeded in creating an interesting learning process, for example educational games, combining play and learning, examples of educational games that are often used are assembler edu, wordwall and Construct 2. This socialization activity took place in the Bina Bangsa IT SMP Hall involving 39 7th grade students. This activity was attended by the Principal and the Teacher Council with resource persons Mrs. Desty Endrawati Subroto M.Pd.